2021
DOI: 10.1007/s11356-021-15473-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between ozone exposure and prevalence of mumps: a time-series study in a Megacity of Southwest China

Abstract: In the present study, we aim to evaluate the delayed and cumulative effect of ozone (O 3 ) exposure on mumps in a megacity with high population density and high humidity. We took Chongqing, a megacity in Southwest China, as the research area and 2013-2017 as the research period. A total of 49,258 confirmed mumps cases were collected from 122 hospitals of Chongqing. We employed the distributed lag nonlinear models with quasi-Poisson link to investigate the relationship between prevalence of mumps and O 3 exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Pulmonary macrophages play an important role in binding and clearing of inhaled particulate matter (Arredouani et al, 2004;Arredouani et al, 2006), whereas exposure to PM 2.5 decrease the antimicrobial activity of pulmonary macrophages (Migliaccio et al, 2013), which probably increased the body's susceptibility for respiratory tract infections. Xie et al (Xie et al, 2021) reported that Ozone exposure can increase the risk of mumps infection. A possible reason is that environmental pollutants can impair ciliary structure and function to impact mucociliary clearance, and can result in lower respiratory tract disease (Cao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary macrophages play an important role in binding and clearing of inhaled particulate matter (Arredouani et al, 2004;Arredouani et al, 2006), whereas exposure to PM 2.5 decrease the antimicrobial activity of pulmonary macrophages (Migliaccio et al, 2013), which probably increased the body's susceptibility for respiratory tract infections. Xie et al (Xie et al, 2021) reported that Ozone exposure can increase the risk of mumps infection. A possible reason is that environmental pollutants can impair ciliary structure and function to impact mucociliary clearance, and can result in lower respiratory tract disease (Cao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated by the world health organization (WHO) that ambient air pollution was responsible for approximately 7 million deaths globally in 2019, accounting for more than 15% of all deaths [9,10]. The COVID-19 pandemic has further highlighted the relationship between air pollution and human health, with studies suggesting that exposure to air pollution can increase the severity of COVID-19 symptoms and mortality rates [11][12][13]. Long-term exposure to air pollutants such as ozone and particulate matter has been linked to an increased risk of respiratory and cardiovascular diseases, leading to more hospitalizations and premature deaths [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…According to the State of the World’s Air 2020, air pollution led to 6.67 million deaths worldwide in 2019, and particulate matter (PM) is the greatest threat to human health, especially as a risk factor in respiratory diseases [ 8 , 9 ]. A study by Zhang et al [ 10 ] found a significant positive association between PM2.5 and mumps, whereas Xie and his colleagues [ 11 ] found no such relationship in Chongqing, and the discrepancy may be related to differences in the scopes of the two studies. So far, the fact that meteorological factors significantly affect mumps is beyond doubt, but the mechanism has not been clarified.…”
Section: Introductionmentioning
confidence: 99%